2000
DOI: 10.1177/154596830001400304
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Postlesion Experience on Behavioral Recovery and Neurophysiologic Reorganization after Cortical Injury in Primates

Abstract: Previous studies have shown that after injury to the hand representation in primary motor cortex (M1), size of the spared hand representation decreased dramatically unless the unimpaired hand was restrained and monkeys received daily rehabilitative training using the impaired fingers. The goal of this study was to determine if restriction of the unimpaired hand was sufficient to retain spared hand area after injury or if retention of the spared area required repetitive use of the impaired limb. After infarct t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 31 publications
7
67
0
1
Order By: Relevance
“…Indeed, intracortical microstimulation and fMRI studies have found that electrophysiological maps can reorganize after cortical stroke in order to compensate for the functional loss in the stroke infarct. Better behavioural outcome is also correlated with the extent of cortical map reorganization (Castro-Alamancos and Borrel, 1995;Friel et al, 2000;Frost et al, 2003;Gharbawie et al, 2005;Kleim et al, 2003;. This cortical reorganization may be mediated by two mechanisms.…”
Section: Electrophysiological Changesmentioning
confidence: 98%
“…Indeed, intracortical microstimulation and fMRI studies have found that electrophysiological maps can reorganize after cortical stroke in order to compensate for the functional loss in the stroke infarct. Better behavioural outcome is also correlated with the extent of cortical map reorganization (Castro-Alamancos and Borrel, 1995;Friel et al, 2000;Frost et al, 2003;Gharbawie et al, 2005;Kleim et al, 2003;. This cortical reorganization may be mediated by two mechanisms.…”
Section: Electrophysiological Changesmentioning
confidence: 98%
“…Subtotal motor cortical lesions disrupt the functional integrity of remaining motor cortical areas . However, practice in skilled reaching improves post-lesion reaching deficits and reinstates motor maps Friel et al, 2000;Conner et al, 2005;Ramanathan et al, 2006). Disruption of motor cortical plasticity decreases reaching performance (Kleim et al, 2003a;Luft et al, 2004).…”
Section: Cortical Stimulation Promotes Synaptic Changes Which Are Cormentioning
confidence: 99%
“…An index of motor performance (finger flexions per food pellet retrieved during post-infarct assessment divided by baseline finger flexions per food pellet retrieved) was derived to control for individual differences in baseline motor skill (Friel et al 2000). A motor performance index of "1" means that pre-and post-infarct performance was equal, an index greater than "1" indicates that the monkey made more finger flexions to retrieve pellets after the infarct, and an index less than "1" indicates that post-infarct performance was improved from pre-infarct performance.…”
Section: Statistical Analysis Of Behavioral Datamentioning
confidence: 99%